Spinach powder as soil conditioner enhances physiochemical properties of soil and growth characteristics of Solanum melongena - Hifza Javed; shazia Iram; Barira Bilal; Tehreem Tassawar (International Journal of Recycling of Organic Waste in Agriculture)
Purpose (i) To evaluate the efficacy of spinach in dry powdered and liquid form as a sustainable substitute for chemical fertilizers; (ii) To analyze and compare the morphological and yield-related parameters of Solanum melongena plants using spinach powder and compost as compared to the control treatment.Method In a pot experiment, Solanum melongena seeds were sowed in soil mixed with spinach powder and compost while the control pots were without any amendment to the soil. The spinach -amended soil, compost-amended soil, and control soil sample were compared in terms physiochemical characteristics like pH , EC ,TDS, organic matter , nutrients i.e. nitrogen , phosphorus, potassium ,calcium ,magnesium and heavy metals. While, plant morphological traits plant height, root length, numbers of flowers and fruits were recorded.Results The pH of spinach-amended soil was slightly alkaline before plantation as compared to control soil. The nitrogen, phosphorus, and potassium content in spinach dry powder was 15%, 36% and 49%, respectively. The organic carbon content was 56% with moderate amount of micronutrients like calcium, magnesium and iron. Spinach powder-amended soil significantly improved the plant morphological characteristics like stem height, root length and able to produce more flowers and mature fruits as compared to compost-amended soil and control soil.Conclusion The use of spinach in powder and liquid concoction was a suitable alternative to chemical fertilizers. It was able to deliver all major macro- and micronutrients to soil thus improving the fertility and has significant impact on plant growth and yield.